PSYCHOLOGICAL FACTORS OF THE FORMATION OF LEADERSHIP QUALITIES IN SCHOOL STUDENTS (International Conference on Modern Science and Scientific Studies, 2025)
This article is devoted to the psychological factors of the formation of leadership qualities in students, and involves the study of the professional, life, scientific, and psychological preparation of high school students. Also, the content of the article, through reliable sources, illuminates the individual characteristics of students, their psychological image and functions on a scientific basis.